Doing “Life”: An Exploratory Study of the Experiences and Implications of Incarceration on Life-Serving Offenders - Gweba, Ntombizanele (Department of Social Development, 2023)
The Department of Correctional Services in South Africa currently incarcerates more than 160,000 offenders, which is ranked ninth in the world and the highest in Africa. The number of life-serving offenders increased from 433 in 1995 to 13,847 in 2014. This constitutes a psycho-social burden on both offenders, their families and society as a whole. Despite this, very little scholarly research has been conducted on the lived experiences of life-sentenced offenders. This study seeks to address this by exploring the realities, experiences, and implications of serving a life sentence among offenders in the Department of Correctional Services. Using a representative voluntary sample of sixteen male life-serving offenders, a qualitative, exploratory approach using semistructured schedules for face-to-face interviews was conducted at Voorberg Correctional Centre in the Western Cape of South Africa. The findings reveal high levels of trauma and mental health challenges being faced daily by those sentenced to life imprisonment. Subsequently, high levels of hopelessness, helplessness, and fear were identified among participants. The study also identified the role of gangs in a correctional facility and overcrowding as a significant obstacle that life-serving offenders are confronted with and that impact their mental health. This study provides a comprehensive set of recommendations involving the cooperation and coordination of all criminal justice stakeholders. Additionally, there is a need for the Department of Correctional Services (DCS) to prioritise the strengthening of human resources, including professionals, provide resources, increase vocational training opportunities for offenders and improve infrastructure within correctional centres. The study concludes that not enough is known about the challenges faced by life sentence offenders and considerably more research needs to be carried out.